Diagnostic evaluation of causes of bleeding per vagina in pregnancy through ultrasonography - K. K., Sumathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Vaginal bleeding is a common obstetric situation ranging from an insignificant episode to life threatening emergency. Ultrasonography is playing an increasing role in the diagnostic process. The objective of present study was to evaluate the uses of ultrasound as new diagnostic aid for patients of bleeding PV in pregnancy. Methods: A hospital-based prospective study was conducted among 100 pregnant patients who have the problem of bleeding. A complete general physical and pelvic examination was done, and patients were then subjected to ultrasound examination. Epi info 7 software was used for statistical analysis. Chi- square test was used as the test of significance. P<0.05 is considered statistically significant. Results: Among these 100 cases, Incomplete abortion was the commonest cause of bleeding. This was observed in 15 cases (27%). There were 8 (20%) cases of complete abortion in the present study in the scan done on <20 weeks. Abruptio placenta was seen in 10 (25%) cases as the most common cause in the scan after 20 weeks. Conclusions: Ultrasound is a valuable tool in the differentiation of causes of first trimester vaginal bleeding. Ultrasound is helpful in the decision-making algorithm about the safe continuation of the pregnancy, timely intervention for abnormal pregnancy.